2022
DOI: 10.1111/acv.12835
|View full text |Cite
|
Sign up to set email alerts
|

Using public surveys to rapidly profile biological invasions in hard‐to‐monitor areas

Abstract: Understanding the impact and dynamics of invasive alien species (IAS) is essential for tailoring appropriate management plans. This information can be difficult to obtain in the short term, and intrinsic difficulties of monitoring hard‐to‐reach areas may hamper prompt estimation of IAS distributions. Using the case of the invasive Asian common toad (Duttaphrynus melanostictus) in Madagascar, we show how public surveys coupled with a multi‐analytical approach can promptly provide accurate information on invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Thirty-five individuals at site 1, 26 at site 2, 20 at site 3, 9 at site 4, and 11 at site 5 were collected (see Tables S1 and S2 ). A detailed description of sampling sites 1–3 can be found in Santos et al [ 16 ], while that of the sites 4 and 5 can be found in Licata et al [ 17 ]. The climate of the study area is characterized by monthly stable temperatures (ranging from 21 °C in July and 27 °C in February) and by the occurrence of alternating dry (between May and September) and moist (between October and April) seasons [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-five individuals at site 1, 26 at site 2, 20 at site 3, 9 at site 4, and 11 at site 5 were collected (see Tables S1 and S2 ). A detailed description of sampling sites 1–3 can be found in Santos et al [ 16 ], while that of the sites 4 and 5 can be found in Licata et al [ 17 ]. The climate of the study area is characterized by monthly stable temperatures (ranging from 21 °C in July and 27 °C in February) and by the occurrence of alternating dry (between May and September) and moist (between October and April) seasons [ 18 ].…”
Section: Methodsmentioning
confidence: 99%